2003
DOI: 10.1046/j.1474-919x.2003.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil particle composition affects the physical characteristics of Sand Martin Riparia riparia holes

Abstract: The importance of correlations between soil particle composition and the physical characteristics of Sand Martin Riparia riparia breeding holes has received very little attention. I used dry sieve analysis and decantation to examine 14 particle size ranges of samples from 654 breeding holes collected at 106 breeding colonies in the Czech Republic and at three in Great Britain. All five measured physical characteristics (tunnel depth, width and height of the entrance opening, slope of the tunnel and the distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 13 publications
2
17
0
2
Order By: Relevance
“…Based on my previous observations, I hypothesized that Sand Martins do not dig their holes in either too loose or too hard soils. Soil hardness is partially related to the content of clay particles (Gupta and Allmaras 1987;Ball et al 2000), thus some support for this hypothesis originated from previous measurements of soil granulometric properties (Heneberg 2001(Heneberg , 2003. But as sand and silt particles joined by clay bridges and precipitated salts form macropores that undergo significant volume decrease when loaded or wet (Francisca 2007), direct measurements of the penetrability resistance were needed to support this hypothesis with more robust data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on my previous observations, I hypothesized that Sand Martins do not dig their holes in either too loose or too hard soils. Soil hardness is partially related to the content of clay particles (Gupta and Allmaras 1987;Ball et al 2000), thus some support for this hypothesis originated from previous measurements of soil granulometric properties (Heneberg 2001(Heneberg , 2003. But as sand and silt particles joined by clay bridges and precipitated salts form macropores that undergo significant volume decrease when loaded or wet (Francisca 2007), direct measurements of the penetrability resistance were needed to support this hypothesis with more robust data.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports dealt with the clay content and stated that the clay content should generally be < 10% (Petersen 1955;Svensson 1969). More exact data regarding soil granulometry appeared just after the turn of the millenium, when Heneberg (2001Heneberg ( , 2003 and Lind et al (2002) published granulometric data related to Sand Martin breeding banks. Yuan et al (2006a, b) did the same with Blue-tailed Bee-eaters (Merops philippinus), Heneberg and Sˇimecˇek (2004) did so for the European Bee-eaters, and Heneberg (2004) did so for Eurasian Kingfishers.…”
Section: Introductionmentioning
confidence: 99%
“…The sand martin is perhaps the best known of the loess-living birds (and has been studied at length by, in particular, Heneberg 2003Heneberg , 2009). This paper is about the ground rather than the birds, and the birds might be seen as experimental operators who manipulate the ground thus enabling its properties to be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…They found that different soil particle sizes influence where species nest and at least partially explain why certain species do not co-nest. Heneberg (2003) also found that the length of the nest tunnel of sand martins increases with an increasing proportion of fine soil particles, which is therefore also associated with breeding success. More studies are needed to investigate the effects of soil chemical and physical properties, not only as they influence nesting-site selection but also breeding success of blue-tailed bee-eaters.…”
Section: Resultsmentioning
confidence: 93%
“…Sandy soils probably allow faster and easier excavation of nest cavities, and provide better drainage (Brooks and Davis 1987) and diffusion of gases to maintain a tolerable level of O 2 and CO 2 in the nest cavities (White et al 1978). Heneberg (2001Heneberg ( , 2003Heneberg ( , 2004 and Heneberg and Simecek (2004) analyzed soil particle sizes for cliff-nesting sand martins (Riparia riparia), Euroasian kingfishers (Alcedo atthis) and European beeeaters. They found that different soil particle sizes influence where species nest and at least partially explain why certain species do not co-nest.…”
Section: Resultsmentioning
confidence: 99%